2019
DOI: 10.1055/s-0039-1688934
|View full text |Cite
|
Sign up to set email alerts
|

The Ratio of Factor VIIa:Tissue Factor Content within Microvesicles Determines the Differential Influence on Endothelial Cells

Abstract: Tissue factor (TF)-positive microvesicles from various sources can promote cellular proliferation or alternatively induce apoptosis, but the determining factors are unknown. In this study the hypothesis that the ratio of fVIIa:TF within microvesicles determines this outcome was examined. Microvesicles were isolated from HepG2, BxPC-3, 786-O, MDA-MB-231, and MCF-7 cell lines and microvesicle-associated fVIIa and TF antigen and activity levels were measured. Human coronary artery endothelial cells (HCAECs) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 52 publications
3
24
0
1
Order By: Relevance
“…Future studies should also determine the precise composition of EMV Pg as their content is clearly influenced by the quantity and type of cellular stress trigger. Indeed, a specific insight should be made on mRNA, miRNA, proteins and membrane receptors 64,74,75 .…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should also determine the precise composition of EMV Pg as their content is clearly influenced by the quantity and type of cellular stress trigger. Indeed, a specific insight should be made on mRNA, miRNA, proteins and membrane receptors 64,74,75 .…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Moreover, the examination of MDA-MB-231 cell line with a monoclonal antibody, indicated the low level expression of the zymogen form of fVII. 42 However, our previous 43 and current examination of cell lines including MDA-MB-231 cells demonstrates the presence of heavy and light chains of the activated form of fVIIa. The expression of fVIIa in MDA-MB-231 cell line was also corroborated by analysing the expression of fVII mRNA in the cells by RT-PCR 43 but was lower in AsPC-1 cell line.…”
Section: Cancer Cell-derived Microvesicles Contain Functional Tf and mentioning
confidence: 91%
“…42 However, our previous 43 and current examination of cell lines including MDA-MB-231 cells demonstrates the presence of heavy and light chains of the activated form of fVIIa. The expression of fVIIa in MDA-MB-231 cell line was also corroborated by analysing the expression of fVII mRNA in the cells by RT-PCR 43 but was lower in AsPC-1 cell line. Moreover, no detectable endogenous fXa antigen was present.…”
Section: Cancer Cell-derived Microvesicles Contain Functional Tf and mentioning
confidence: 91%
“…Cell numbers were determined by staining with crystal violet as previously described [50,51] and calculated from a standard curve. In addition, cellular apoptosis was quantified using the TiterTACS™ Colorimetric Apoptosis Detection Kit (AMS Biotechnology, Abingdon, UK) according to the manufacturer's instructions and as described before [18,19]. The criteria for endothelial cell apoptosis were evaluated according to the published consensus guidelines [52] and the apoptosis established as described previously [53].…”
Section: Cell Proliferation and Apoptosis Assaysmentioning
confidence: 99%
“…Furthermore, TF is capable of inducing cellular apoptosis through intracellular signalling mechanisms [15][16][17]. Recently, we reported that the accumulation of TF within endothelial cells, either through increased retention, or by acquisition of TF can promote cellular apoptosis [18,19] through mechanisms mediated by p38 mitogen-activated protein kinases (MAPKs) [18]. TF-VIIa complex is capable of activating protease activated receptor (PAR)-2 which results in cellular signalling directly [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%